2012
DOI: 10.1590/s2176-94512012000600018
|View full text |Cite
|
Sign up to set email alerts
|

Relation between agenesis and shape anomaly of maxillary lateral incisors and canine impaction

Abstract: Objective:The purpose was to obtain information about the relation between agenesis and shape anomaly of maxillary lateral incisors and canine impaction. Methods: Seventy-three patients with canine impaction and 73 control patients, without canine impaction, were evaluated. The mesiodistal distances of the maxillary lateral incisors adjacent to the impacted canines and the correspondent mandibular lateral incisors were measured. The adjacent lateral incisors were classified in: 1 -absent, 2 -small, 3 -peg-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…Our previous and present studies show that there is a connection between impacted canines and other dental anomalies and these facts concur with the work of Carvahlo et al [7], Paschos et al [8], Peck et al [9], Sacerdoti [10], Leifert [11], Langberg [12], Mesotten et al [13], Nagpal et al [14]. The reason for this incidence in the specialty literature about this relation is that the surplus of space in the maxilla could be a contributing factor for the canine misplacement and subsequently impaction as it allows enough space for the canine to depart its normal direction of eruption.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our previous and present studies show that there is a connection between impacted canines and other dental anomalies and these facts concur with the work of Carvahlo et al [7], Paschos et al [8], Peck et al [9], Sacerdoti [10], Leifert [11], Langberg [12], Mesotten et al [13], Nagpal et al [14]. The reason for this incidence in the specialty literature about this relation is that the surplus of space in the maxilla could be a contributing factor for the canine misplacement and subsequently impaction as it allows enough space for the canine to depart its normal direction of eruption.…”
Section: Discussionsupporting
confidence: 94%
“…In the recent past we have conducted similar studies to observe the two different canine pathologies and our conclusions were similar to this present study [6,7].…”
Section: Discussionsupporting
confidence: 91%
“…The canine will not erupt if the root of the lateral incisor is missing or deformed. 6,7 The deciduous lateral incisor is still maintained in the end of treatment. It is not replaced.…”
Section: Discussionmentioning
confidence: 99%
“…Nagpal et al; (19) ; found that in a sample of palatally impacted canines, the mesiodistal diameter of maxillary incisors crown was less than that of the control group. Also, Carvalho et al; (20) in their work concluded that the appearance of small sized permanent incisors in initial permanent dentition may be an indicator of future impaction of the canines, especially if it is combined with other dental anomalies. However, Jacoby found crowding in 15% of palatally impacted canine cases.…”
Section: Volume 49 -June 2016mentioning
confidence: 99%